2008
DOI: 10.1007/s00213-008-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 increases anxiety- and fear-related behaviors in the rat

Abstract: These findings suggest that in addition to its role as a satiety peptide, nesfatin-1 may also be involved in the mediation of anxiety- and/or fear-related responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 58 publications
(64 reference statements)
9
76
0
7
Order By: Relevance
“…Central injection of CART and nesfatin/NUCB2 into male rodents increases anxiety (Koylu et al, 2006;Merali et al, 2008). This is in line with our observation of increased CART and nesfatin/NUCB2 mRNA expressions in depressed suicide victims.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Central injection of CART and nesfatin/NUCB2 into male rodents increases anxiety (Koylu et al, 2006;Merali et al, 2008). This is in line with our observation of increased CART and nesfatin/NUCB2 mRNA expressions in depressed suicide victims.…”
Section: Discussionsupporting
confidence: 91%
“…The results extend prior observations on the possible involvement of CART and nesfatin/NUCB2 in MDD in humans (Ari et al, 2011;Miraglia del Giudice et al, 2006) and in anxiety-and depressive-like behaviour in rodents (Dandekar et al, 2008;Garcia-Galiano et al, 2010;Merali et al, 2008;Wiehager et al, 2009) in a number of ways. Firstly, we showed that CART and nesfatin-1 were present and colocalized in EWcp neurons.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most of the authors working on rats and using icv injections investigating different aspects of nesfatin-1's actions have also found the 5 --20 pmol dose range effective, higher doses only caused earlier timing of the effect, and/or enhanced the tendencies observed with lower dose. 5,22,23 We also found the 25 pmol dose as an adequate one, increasing the dose to 100 pmol did not lead to any substantially new observations. Long-lasting effects and interference with the diurnal rhythm are not exclusive among the peptides regulating energy balance.…”
Section: Discussionmentioning
confidence: 53%
“…It stimulates autonomic nervous system activity, increases blood pressure (53), and has been associated with a range of brain functions, including the regulation of feeding. Nucleobindin induces fear and anxiety in rats (54). Nesfatin-1 also elevates the intracellular concentration of Ca 2Ï© in mouse neurons and causes calcium signaling via calcium influx through Ca V 2.2 calcium channels (55).…”
Section: Resultsmentioning
confidence: 99%